Socio-urban Metabolic Impact in State of México, México 2010-2020 - Montoya, Dainiz (2024)
The State of Mexico is a Mexican entity facing socio-environmental problems: destruction of forest resources, water and air pollution, and poor quality of basic services. This paper analyzes its socio-urban metabolism between 2010 and 2020, considering it as a thermodynamic machine. Using Material Flow and Energy Flow Analysis (MFAE), indicators of consumption and emissions of electricity, fuel, water and social aspects (schooling, social security, economically active population and PBT) were obtained. Metabolic Indexes (MI) were calculated to indicate consumption by municipality. The results showed increases in: fuel consumption (275%), water (130%) and decrease in electricity consumption (-65.7%) due to costs, overcrowding and theft, indicating a governmental inability to provide services. On the social issue, the quality of education declined despite the decrease in the illiterate population. Access to social security rose (27%) in 2020, but public entities are bankrupt and 47.9% of the population is poor. The MI showed that the most consuming municipalities are those in the Toluca Valley and those in the suburbs of Mexico City. Despite the alignment of urban planning to the SDGs, they are not achieved due to methodologies that do not contemplate thermodynamic laws, socio-environmental complexity and, therefore, long-term sustainability.